“The Less I Think About It, the Better I Feel”: A Thematic Analysis of the Subjective Experience of Malignant Mesothelioma Patients and Their Caregivers - Guglielmucci, Fanny; Franzoi, Isabella G.; Bonafede, Michela; Borgogno, Francesca V.; Grosso, Federica; Granieri, Antonella (Frontiers in Psychology, 2018)
Aim: A cancer diagnosis – and in particular a Malignant Mesothelioma (MM) one – breaks the somatopsychic balance of the individual, compromising the quality of residual life and giving rise to many negative emotions difficult to integrate and to elaborate (such as depression, fears, anxieties, hopelessness, guilt, shame and rage). Several national and international guidelines acknowledged the importance of evaluating psychological and socio-relational features in MM patients and their caregiver. However, only few studies have investigated the subjective experience of MM patients and even less research has focused on the caregivers’ experience. Thus, the aim of the present study is to investigate the lived experience of both MM patients and their caregivers, providing an in-depth comprehension of the psychological sequelae of the disease. Material and Methods: Within a psychoanalytically-informed conceptual framework, open-ended interviews were conducted with 10 MM patients and 9 caregivers. Thematic analysis was employed: interviews were audio-recorded, transcribed verbatim and coded in order to identify the main recurring themes across the narratives. Results: We detected four different themes: 1) bodily symptoms and embodied emotions; 2) living in or near a National Priority Contaminated Site (NCPS); 3) “nothing is like it was” (that is, the impact of the diagnosis on everyday life, the changes it causes in the family relationships, the things that are still possible to do, the mourning process); 4) “what will become of us?” (that is, worries about the impact of the diagnosis on the beloved ones, death and legacy). Discussion: MM patients and careers seem to be stuck in a concrete mental functioning focused on symptoms and they find it difficult to openly think and talk about the affective and emotional consequences of the diagnosis. Alongside this, they express the need to find new and less conflictual ways to stay together and talk to each other during the period of active treatments for the illness (i.e. chemotherapy, radiotherapy, etc) and the end-of-life. The results of this study have important implications for the clinical management of MM and can help develop multi-professional specialist interventions addressed to both patients and caregivers.